Management of Temporomandibular Joint Dysfunction Syndrome: An Overview (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Temporomandibular joint dysfunction is a complex and multifactorial disorder of oro-facial region. It is one of the most common disorders in maxillofacial region. The usual complain of the patients with this syndrome are pain in the area of the jaw and associated muscles, eating problem, chewing and locking of the jaw. It is more common in female than male. Its etiology is not yet well established. However its successful management depends on identification and controlling of the etiological factors.J Bangladesh Coll Phys Surg 2017; 35(3): 133-141